1993
DOI: 10.1073/pnas.90.21.10300
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase A antagonizes platelet-derived growth factor-induced signaling by mitogen-activated protein kinase in human arterial smooth muscle cells.

Abstract: Stimulation ofaortic smooth muscle cells with platelet-derived growth factor BB homodimer (PDGF-BB) leads to the rapid activation ofmitogen-activated protein kinase (MAPK) and MAPK kinase (MAPKK). Compounds that increase cAMP and activate protein kinase A (PKA) prostaglandin E2, isoproterenol, cholera toxin, and forskolinwere found to inhibit the PDGF-BB-induced activation of MAPKK and MAPK. Forskolin, but not the inactive analogue 1,9-dideoxyforskolin, inhibited PDGF-BB-stimulated MAPKK and MAPK activation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
292
4

Year Published

1996
1996
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 442 publications
(316 citation statements)
references
References 39 publications
20
292
4
Order By: Relevance
“…Therefore, tumors that express two or more of these growth factors may require a cocktail of anticancer drugs. In contrast, b2AR stimulation will block activation of the Raf-1/Mek-1/Erk1/2 pathway when it is driven by several growth factors as they all require Mek to activate Erk1/2 (Graves et al, 1993;Sevetson et al, 1993;Wu et al, 1993;Sebolt-Leopold, 2000;Dumaz and Marais, 2005). For example, we have shown that growth factor (i.e., EGF) stimulation of P-Erk1/2 is blocked by ARA-211 in MDA-MB-231 cells (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, tumors that express two or more of these growth factors may require a cocktail of anticancer drugs. In contrast, b2AR stimulation will block activation of the Raf-1/Mek-1/Erk1/2 pathway when it is driven by several growth factors as they all require Mek to activate Erk1/2 (Graves et al, 1993;Sevetson et al, 1993;Wu et al, 1993;Sebolt-Leopold, 2000;Dumaz and Marais, 2005). For example, we have shown that growth factor (i.e., EGF) stimulation of P-Erk1/2 is blocked by ARA-211 in MDA-MB-231 cells (data not shown).…”
Section: Discussionmentioning
confidence: 81%
“…However, it should be noted here that G s stimulates proliferation only in the cells ± such as those present in endocrine tissues ± that are positively responsive to cAMP-PKA signaling pathway for their cell growth. By contrast, in other cells, Ga s appears to have a growth inhibitory e ect through its negative regulation of Ras-Raf signaling pathway (Burgering et al, 1993;Graves et al, 1993;Cook and McCormick, 1993;Wu et al, 1993;Sevetson et al, 1993). In these cell types, PKA activated by Ga s through cAMP directly phosphorylates Raf at Ser 43 and/or Ser 671 Mischak et al, 1996) thus inhibiting Raf and its downstrean MEK-ERK cascade.…”
Section: Ga S and The Gsp Oncogenementioning
confidence: 99%
“…A case to the point is the ability of cAMP from G s signaling pathway to inhibit ERK-signaling pathway (Burgering et al, 1993;Graves et al, 1993;Cook and McCormick, 1993;Wu et al, 1993;Sevetson et al, 1993). Recently it has been shown that during genotoxic stress, p53, the well characterized tumor suppressor, downregulates the activity of Ga q and Ga 11 through Ga q/11 -speci®c RGS protein (Buckbinder et al, 1997), a negative regulator of G protein activity (Berman and Gilman, 1998).…”
Section: G Protein Interactions With Other Signaling Pathwaysmentioning
confidence: 99%
“…Several recent studies have shown the existence of cross-talk between the MAP kinase pathways, a key pathway in the regulation of cell growth and differentiation, and cAMP. [17][18][19][20][21][22][23][24] This relationship may provide a biochemical explanation for the divergent effects of cAMP on cell growth in different cell types. In cells such as fibroblasts, adipocytes, or vascular smooth muscle cells, in which cAMP inhibits proliferation, increasing cAMP blocks the activation of the MAP kinase pathway by growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…In cells such as fibroblasts, adipocytes, or vascular smooth muscle cells, in which cAMP inhibits proliferation, increasing cAMP blocks the activation of the MAP kinase pathway by growth factors. [17][18][19][20][21][22] By contrast, in cells in which cAMP stimulates proliferation or differentiation, such as PC12 cells, elevation of intracellular cAMP activates the MAP kinase cascade. 23,24 The role of cAMP in the control of hepatocyte prolifer- EGF.…”
Section: Discussionmentioning
confidence: 99%